2002
DOI: 10.1126/science.1075035
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Photochemical Water Splitting by a Chemically Modified n-TiO 2

Abstract: Although n-type titanium dioxide (TiO2) is a promising substrate for photogeneration of hydrogen from water, most attempts at doping this material so that it absorbs light in the visible region of the solar spectrum have met with limited success. We synthesized a chemically modified n-type TiO2 by controlled combustion of Ti metal in a natural gas flame. This material, in which carbon substitutes for some of the lattice oxygen atoms, absorbs light at wavelengths below 535 nanometers and has a lower band-gap en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
2,045
3
17

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 4,024 publications
(2,098 citation statements)
references
References 19 publications
33
2,045
3
17
Order By: Relevance
“…It was found that TiO 2 modification by non-metals such as carbon (3) causes light absorption in the visible region. For this purpose different inorganic and organic carbon precursors were used (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Wide range of used precursors make it possible to widen TiO 2 activation range of irradiation to visible region.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that TiO 2 modification by non-metals such as carbon (3) causes light absorption in the visible region. For this purpose different inorganic and organic carbon precursors were used (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Wide range of used precursors make it possible to widen TiO 2 activation range of irradiation to visible region.…”
Section: Introductionmentioning
confidence: 99%
“…50 In this context, gold nanoparticles (Au NPs) supported TiO 2 hybrid photocatalytic systems have attracted much attention because of their strong light absorption in the visible region, which arises from enhanced scattering and Localized Surface Plasmon Resonance (LSPR). [9][10][11] Due to LSPR, Au NPs can 55 effectively harvest the electromagnetic energy of the incident light and concentrate it into "plasmonic hotspots", which in turn can maximize the local field intensity by a factor of 10 6 . 12 Notably, one dimensional (1-D) TiO 2 nanostructures such as nanowires, nanotubes, nanofibers etc., afford ample room to 60 accommodate the nanoparticles compared to their bulk counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…TiO2 has been widely used as a photocatalyst for photogeneration of hydrogen from water [12,13] , solar-energy conversion [14], and degradation of organic compounds [15], due to its high oxidative power, chemical stability, low cost, and non-toxicity. Much attention was also focused on its potential application in the electrode material of the lithium-ion battery [16][17][18][19].…”
Section: Accepted Manuscriptmentioning
confidence: 99%